TRAIN HARVESTING UNIT PRODUCTIVITY AS MAN-MACHINE SYSTEM - I.E. LIPKOVICH; N.V. PETRENKO (Advanced Engineering Research)
The problem of grain harvesting unit productivity as MMS is dealt with the method of rational labor regime introduction. The plot of productivity coefficient change are made up by different operating conditions of personnel. The plots consider the influence of man factor on changing of the grain harvesting unit productivity as MMS.